KADAR KOLESTEROL DENGAN KEJADIAN PENDERITA HIPERTENSI - Arif, Muhammad Ridwan; Purnamawati, Ditha Astuti; Rahmawati, Annisa (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Hypertension is a chronic condition characterized by an increase in blood pressure against the walls of arterial blood vessels. One of the factors most frequently associated with elevated blood pressure is dyslipidemia, particularly hypercholesterolemia, which refers to an increased level of total cholesterol in the blood. Elevated cholesterol levels, especially low-density lipoprotein (LDL), can trigger the formation of atherosclerotic plaques on the arterial walls, narrowing the vessel lumen and increasing vascular resistance. It is estimated that approximately 18% of the population, or around 36 million people, experience lipid abnormalities, of which 80% of cases result in sudden death due to heart attack. Objective:This study aimed to determine the relationship between cholesterol levels and the incidence of hypertension among patients in the working area of Sungai Raya Dalam Public Health Center, Sungai Raya District. Methods: This study employed an analytical observational design with a quantitative approach, using a cross-sectional design and purposive sampling method. A total of 97 respondents diagnosed with hypertension at the Sungai Raya Dalam Public Health Center were included as the study sample. Results: The results of the study showed a p-value of 0.000 (<0.05), indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The strength of the relationship was moderate, with a correlation coefficient value of 0.353**. Statistical analysis indicated a positive or unidirectional relationship between the two variables. Conclusion: This study demonstrated a significant relationship between cholesterol levels and increased blood pressure among individuals with hypertension.